Analisis Risiko Keselamatan dan Kesehatan Kerja Awak Kapal Cantrang Menggunakan HIRA di PPP Tegalsari Kota Tegal: - - Singgih Singgih; Adi Susanto; Nurhasanah Nurhasanah (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Cantrang fishing operations involve a high level of occupational safety and health (OSH) risk due to the use of heavy fishing gear, mechanical equipment, and dynamic marine working conditions. This study aimed to identify potential hazards, assess risk levels, and develop occupational safety and health risk control measures for cantrang vessel crews using the Hazard Identification and Risk Assessment (HIRA) method. The study was conducted at Tegalsari Coastal Fishing Port, Tegal City, Indonesia, through field observations, interviews, hazard identification, and risk assessment based on likelihood and severity parameters. The results showed that hauling posed the highest risk (Risk Level = 20), followed by setting and towing (Risk Level = 16), while net arrangement and loading–unloading activities (Risk Level = 12) were classified as high-risk activities. Engine inspection (Risk Level = 9), vessel preparation, and catch sorting (Risk Level = 6) were categorized as moderate-risk activities. Risk control should prioritize the implementation of standard operating procedures (SOPs), routine equipment inspections, the use of personal protective equipment (PPE), and regular safety training for vessel crews. These findings provide a basis for implementing occupational safety and health risk management in cantrang fishing operations.